Enhancing Early Childhood Creativity through Project-Based Learning: Indonesian Traditions at KJRI Penang - Saputri, Wahyu Dwi; Mahardani, Ardhana Januar; Wulansari, Betty Yulia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Project-Based Learning (PjBL) has been recognized for its potential to enhance various skills, including creativity, among learners. However, its impact on early childhood creativity, particularly within specific cultural contexts, remains underexplored. The aim of this research is to evaluate how culturally relevant PjBL activities, incorporating Indonesian traditions, can enhance creativity in early childhood learners at the Indonesian Consulate General (Konsulat Jenderal Republik Indonesia/KJRI) Penang. A mixed-methods approach was employed, combining both qualitative and quantitative data collection. The study involved designing and implementing PjBL activities based on Indonesian traditions over three months. Creativity was assessed using the Torrance Tests of Creative Thinking (TTCT) before and after the intervention. Additionally, qualitative data were collected through classroom observations and semi-structured interviews with teachers and parents. The quantitative analysis of TTCT scores indicated a significant improvement in various aspects of creativity, including fluency, originality, and elaboration, among the children who participated in the culturally enriched PjBL activities. Qualitative data supported these findings, revealing high levels of engagement, creativity, and enthusiasm among the children. Teachers and parents also observed noticeable improvements in the children’s creative thinking and problem-solving abilities. The integration of Indonesian traditions into PjBL activities effectively enhances creativity in early childhood learners. The findings suggest that culturally relevant educational approaches can significantly contribute to the creative development of young children. This study provides valuable insights for educators and policymakers on the implementation of culturally tailored PjBL to foster creativity in diverse educational.